Bio-physical evaluation and in vivo delivery of plant proteinase inhibitor immobilized on silica nanospheres - Khandelwal, Neha; Doke, Dhananjay S.; Khandare, Jayant J.; Jawale, Priyanka V.; Biradar, Ankush V.; Giri, Ashok P. (Colloids and Surfaces B-Biointerfaces, 2015)
Recombinant expression of Capsicum annuum proteinase inhibitors (CanPI-13) and its application via synthetic carrier for the crop protection is the prime objective of our study. Herein, we explored proteinase inhibitor peptide immobilization on silica based nanospheres and rods followed by its pH mediated release in vitro and in vivo. Initial studies suggested silica nanospheres to be a suitable candidate for peptide immobilization. Furthermore, the interactions were characterized biophysically to ascertain their conformational stability and biological activity. Interestingly, bioactive peptide loading at acidic pH on nanospheres was found to be 62% and showed 56% of peptide release at pH 10, simulating gut milieu of the target pest Helicoverpa armigera. Additionally, in vivo study demonstrated significant reduction in insect body mass (158 mg) as compared to the control insects (265 mg) on 8th day after feeding with CanPI-13 based silica nanospheres. The study confirms that peptide immobilized silica nanosphere is capable of affecting overall growth and development of the feeding insects, which is known to hamper fecundity and fertility of the insects. Our study illustrates the utility and development of peptide-nanocarrier based platform in delivering diverse biologically active complexes specific to gut pH of H. armigera. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Biodelivery; Helicovera armigera; Protein `corona'; Proteinase inhibitor; Silica nanospheres

Bicinchoninic acid-based colorimetric chemosensor for detection of low concentrations of cyanide - Biradar, Archana A.; Biradar, Ankush V.; Sun, Tiffany; Chan, Yung; Huang, Xiaoxi; Asefa, Tewodros (Sensors and Actuators B-Chemical, 2016)
Bicinchoninic acid (BCA) is reagent that is widely used to determine the concentration of proteins in solutions through the colored complex it forms with Cu(I) and the proteins. In this report, we present a new use for BCA, where a highly sensitive method for detection of cyanide ions in solutions by using Cu2+-BCA complex as the chemosensing agent is demonstrated. The detection of cyanide ions is achieved by taking advantage of the nucleophilic attack of the Cu2+-BCA complex by cyanide ions. Upon the addition of cyanide ions, the Cu2+-BCA complex undergoes transformations to free BCA via a series of equilibriums and, as a result, forms different Cu(II)-(BCA)(x)(CN)(y) species depending on the concentrations of cyanide ions in the solution. These different Cu(II)-(BCA)(x)(CN)(y) species, in turn, give different metal-to-ligand charge transfer electronic spectra and colors that are easily detectable both with naked eyes and UV-vis spectroscopy. As the cyanide ion concentration increases, the color of the solution containing the complexes changes from green to purple, red, yellow, and finally colorless, giving a corresponding blue shift in the absorption maxima on their UV-vis spectra. Through this process, the complexes enable detection of cyanide ions with a detection level of up to 0.06 ppm in solutions. Thus, this colorimetric technique based on Cu2+-BCA can make low concentrations of cyanide detectable, well before the concentrations possibly reach lethal amounts. Furthermore, the method is shown to give fast detection response with no interference from other anionic and cationic species and has the potential to be adopted for accurate and convenient analysis of cyanide ions in drinking water sources as well as industrial effluents. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: BCA; Bicinchoninic acid; Chemosensor; Colorimetric sensor; Copper; Cyanide

Budding trends in integrated pest management using advanced micro- and nano-materials: challenges and perspectives - Khandelwal, Neha; Barbole, Ranjit S.; Banerjee, Shashwat S.; Chate, Govind P.; Biradar, Ankush V.; Khandare, Jayant J.; Giri, Ashok P. (Journal of Environmental Management, 2016)
One of the most vital supports to sustain human life on the planet earth is the agriculture system that has been constantly challenged in terms of yield. Crop losses due to insect pest attack even after excessive use of chemical pesticides, are major concerns for humanity and environment protection. By the virtue of unique properties possessed by micro and nano-structures, their implementation in Agri-biotechnology is largely anticipated. Hence, traditional pest management strategies are now forestalling the potential of micro and nanotechnology as an effective and viable approach to alleviate problems pertaining to pest control. These technological innovations hold promise to contribute enhanced productivity by providing novel agrochemical agents and delivery systems. Application of these systems engages to achieve: i) control release of agrochemicals, ii) site-targeted delivery of active ingredients to manage specific pests, iii) reduced pesticide use, iv) detection of chemical residues, v) pesticide degradation, vi) nucleic acid delivery and vii) to mitigate post-harvest damage. Applications of micro and nano-technology are still marginal owing to the perception of low economic returns, stringent regulatory issues involving safety assessment and public awareness over their uses. In this review, we highlight the potential application of micro and nano-materials with a major focus on effective pest management strategies including safe handling of pesticides. (C) 2016 Elsevier Ltd. All rights reserved.